(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
he study was carried of Korfball, Swimmer and Thrower. It was hypothesis that there might be significant difference in the cardio-vascular endurance of Korfballer, Swimmer and Thrower. It was also hypothesis that the cardio vascular endurance of Korfballer and Swimmer will be more that thrower. For the purpose of this study total 30 subjects were selected. There were 10 players from each game. These were the players who took part in the inter-collegiate competition, S.G.B. Amravati University, Amravati. The subjects were in the age group of 18 to 25 years, only male players were taken for the study.